FACING THE NOVICE TEACHER’S STAGE - Widiarti Hasanah (Institut Pendidikan Indonesia Garut, 2020)
This study aims to investigate the experience that faced by novice English teacher in teaching English. To achieve the aforesaid purpose, this study was employed a qualitative study. The data collected through WhatsApp conversations. A novice English teacher of one Senior High School is chosen as participant. The result showed that there are some challenges faced by novice English teacher in teaching process; initial activities, core activities, and closing activities. The novice teacher provides several solutions to deal with these challenges, including in the initial activities stage, core activities stage, and the closing activities stage.